PENERAPAN MODEL PEMBELAJARAN PENEMUAN TERBIMBING (GUIDED DISCOVERY) UNTUK MENCAPAI KETUNTASAN BELAJAR PESERTA DIDIK PADA SUB POKOK BAHASAN IKATAN KIMIA DI KELAS X 7 MIA SMA NEGRI 1 PASIR PENYU - Anggo, Oktri; Linda, Roza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Research about the application of Guided Discovery learning model aims to achieve student’s mastery learning on the topic of the chemical bonding in class X 7MIA Science SMAN 1 Pasir Penyu. Has been done the research used one shot-study case design. The sample was that class X 7 MIA selected from the two existing classes. Data analysis technique used the percentage calculation of mastery learning classical. Based on the results of data processing obtained mastery learning classical of knowledge competency is 90,91%, means that the application of Guided Discovery learning model can achieve student’s mastery learning on the topic of the chemical bonding in class X 7MIA 1 SMAN 1 Pasir Penyu.Keywords : Guided Discovery, Mastery Learning, Chemical Bonding.